2018
DOI: 10.2337/db18-2213-pub
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Type 2 Diabetic Patients With and Without Proliferative Retinopathy and Macular Edema

Abstract: Diabetic retinopathy is the most common diabetic eye disease and a leading cause of blindness in adults. In India diabetes is an epidemic, so the prevalence of diabetic retinopathy is also increasing. The main objective of the study is to compare both health related and vision targeted quality of life of type 2 diabetic patients with and without proliferative diabetic retinopathy or diabetic macular edema. A prospective, observational study was conducted in a tertiary care referral hospital at Kerala, India, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It is imperative to effectively triage patients who are at risk of permanent vision loss. Although to date there are no specific publications describing the impact of DMI on quality of life, the consequences of vision loss in general and DR, specifically on quality of life, are significant and increase with disease severity (p \ 0.0001) [38][39][40].…”
Section: Jacqueline's Experience With Diagnosis Of Vision Lossmentioning
confidence: 99%
“…It is imperative to effectively triage patients who are at risk of permanent vision loss. Although to date there are no specific publications describing the impact of DMI on quality of life, the consequences of vision loss in general and DR, specifically on quality of life, are significant and increase with disease severity (p \ 0.0001) [38][39][40].…”
Section: Jacqueline's Experience With Diagnosis Of Vision Lossmentioning
confidence: 99%
“…Among the microvascular complications of diabetes, diabetic retinopathy (DR) and QoL assessment were reported in three studies. [ 42 52 53 ] One study reported lower QoL among patients with diabetes with diabetic retinopathy (DR) as compared to those without. The study participants included T1D and T2D patients.…”
Section: R Esultsmentioning
confidence: 99%
“…[ 42 ] The third, a prospective, observational study among 189 T2D patients reported a significant reduction in HRQoL with the severity of retinopathy. [ 53 ]…”
Section: R Esultsmentioning
confidence: 99%
See 1 more Smart Citation